2006
DOI: 10.1007/s10661-006-9288-4
|View full text |Cite
|
Sign up to set email alerts
|

Determination of heavy metal pollution with environmental physicochemical parameters in waste water of Kocabas Stream (Biga, Canakkale, Turkey) by ICP-AES

Abstract: Waste water pollution of industrial areas can answer for the serious consequences of one of the most important environmental threats to the future. In this study, inductively coupled plasma-atomic emission spectrometry method (ICP-AES) is proposed to determine heavy metals (Pb, Cu, Cd, Cr, Zn, Al, Fe, Ni, Co, Mn) and major elements (Ca, Mg) in waste water of Kocabas Stream. The concentration of metals in the waste water samples taken from 9 different stations (St.) in Biga-Kocabas Stream in November 2004 (autu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 8 publications
0
21
0
2
Order By: Relevance
“…After the samples were cooled 10 ml (1+1) HCl and 15 ml distilled deionized water were added and evaporated for 15 min. The cooled samples were filtered from blue-band (Whatman 42) and distilled water was added to make 25 ml (Method 200,7 1994;Yayıntaş et al 2006).…”
Section: Study Area and Procedures Of Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…After the samples were cooled 10 ml (1+1) HCl and 15 ml distilled deionized water were added and evaporated for 15 min. The cooled samples were filtered from blue-band (Whatman 42) and distilled water was added to make 25 ml (Method 200,7 1994;Yayıntaş et al 2006).…”
Section: Study Area and Procedures Of Samplingmentioning
confidence: 99%
“…According to literature investigations, the concentrations of heavy metals have not been studied except the one previously carried out by ICP-AES techniques in the Kocabas Stream area (Yayıntaş et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…uptake through food chain). Heavy metals normally occurring in nature are not harmful to the environment, but their presence at higher concentrations become toxic, and pollution in relation to their toxicity to aquatic organisms affect ultimate wellbeing of humans (Canli & Atli, 2003;Yayıntas et al, 2007). Khaled (2004) found that sediment analysis, allows identification of contaminants which are absorbed by particulate matter that escape detection by water analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The anthropogenic activities may include exploitation of forest resources by human activities, conversion of pristine peat swamp forest into oil palm plantation by the traders, deforestation for mitigating wood demand, urban Science Publications AJES development and expansion, industrial and agricultural practices. These activities often results in the degradation of water quality, physical habitat and biological integrity of lotic system (Yayýntas et al, 2007). The effects of timber harvesting on stream water quality and efficiency of alternate streamside management zones has been studied in Pockwock Lake of Nova Scotia, Canada (Vaidya et al, 2008).…”
Section: Introductionmentioning
confidence: 99%